Pendidikan Gender Sebagai Solusi Bagi Kekerasan Berbasis Gender Dalam Rumah Tangga - Ngutra, Don Bosco (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2024)
Humans, both male and female, are glorious creatures of God because they are created in God’s own image. God wants them to be one in the family. However, this noble purpose is facing various kinds of probation, one is violence against woman in the household. This article participates in the Catholic Church’s efforts to promote a vision of Christian anthropology for a more comfortable and harmonious modern family life. This paper aims to present the Catholic Church’s perspective on gender education to enrich the knowledge of ecclesiastical officers, including catechists, as well as to build family and community awareness to prevent gender-based violence in the household. Employing a literature research with an exposition approach, this study finds that education has great potential to form a society that is more aware, empathetic, and understands the importance of gender equality in the family life.